2019
DOI: 10.17802/2306-1278-2019-8-2-87-97
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Vascular Graft Reinforced With a Biodegradable Sheath

Abstract: Background. Tissue-engineered vascular grafts can be reinforced by a biostable or biodegradable polymer sheath. A combination of electrospinning, routinely used for fabrication of biodegradable tubular grafts, and the layer-by-layer coating allows forming a polymeric sheath ensuring long-term integrity and high biocompatibility of the vascular grafts after the implantation. Aim To evaluate mechanical properties and in vivo performance of biodegradable small-diameter vascular grafts with a reinforcing sheath.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The absence of elastic fibers is a considerable and general disadvantage of biodegradable TEVGs, albeit a recent study reported the successful formation of the internal elastic lamina by the embedding of tropoelastin fibers into the poly(glycerol sebacate), a highly elastic and degradable biomaterial, during electrospinning [ 74 ]. Yet, the enclosure of poly(glycerol sebacate) or fibrin scaffold into the PCL [ 75 , 76 ] or poly(glycolic acid) [ 77 ] sheath efficiently prevented the development of aneurysms, similar to our previous work [ 60 ]. The lack of contractile VSMCs under significant cyclic strain characteristic of the ovine carotid artery was unexpected, as this is a major stimulus of such molecular specification [ 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The absence of elastic fibers is a considerable and general disadvantage of biodegradable TEVGs, albeit a recent study reported the successful formation of the internal elastic lamina by the embedding of tropoelastin fibers into the poly(glycerol sebacate), a highly elastic and degradable biomaterial, during electrospinning [ 74 ]. Yet, the enclosure of poly(glycerol sebacate) or fibrin scaffold into the PCL [ 75 , 76 ] or poly(glycolic acid) [ 77 ] sheath efficiently prevented the development of aneurysms, similar to our previous work [ 60 ]. The lack of contractile VSMCs under significant cyclic strain characteristic of the ovine carotid artery was unexpected, as this is a major stimulus of such molecular specification [ 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 64%
“…Previously, our group reported an efficient approach for increasing haemocompatibility and thrombosis prevention by immobilising an anticoagulant heparin and a vasodilator/antiplatelet drug, iloprost, to the luminal surface of PCL-based TEVGs [ 25 ]. Further, we have developed an anti-aneurysmatic PCL sheath attached to the TEVG outer surface by fused deposition modeling, a method employing 3D printing extrusion [ 60 ]. Here, we combined iloprost and a cationic amphiphilic drug (CAD) 1,5-bis-(4-tetradecyl-1,4-diazoniabicyclo [2.2.2] octan-1-yl) pentane tetrabromide, which has higher antibacterial and antiviral properties in comparison with other CADs because of RNAse activity.…”
Section: Discussionmentioning
confidence: 99%